DEVELOPMENT OF E-MAGAZINE ON SUNAN AMPEL RELIGIOUS TOURISM THEME ON THE MATERIALS OF ELEMENTS, COMPOUNDS, AND MIXTURES - Yanti Fatmawati; Dwi Bagus Rendy Astid Putera (Universitas Negeri Surabaya, 2025)
The purpose of this research is to determine the validity and responses of students towards the E-Magazine learning media themed Religious Tourism of Sunan Ampel on the material of elements, compounds, and mixtures. This research is a type of R&D research with the ADDIE development model. The study was conducted in the even semester of the 2024/2025 academic year at SMP Negeri 4 Surabaya with research subjects from class VIII-A and IX-F. This study uses an instrument in the form of a validation questionnaire for media experts and material experts. The results of the study showed that the media expert assessment had a percentage of 91.67%, and the material expert assessment had a percentage of 88.75%. This result is supported by data on student responses to the e-Magazine themed Religious Tourism of Sunan Ampel with a percentage of 82.36%, categorized as very good. Therefore, the research results show that the e-Magazine on the theme of Religious Tourism of Sunan Ampel, regarding the materials of elements, compounds, and mixtures that were developed, is very valid to be used as a media for learning science and received very good responses from the students.